2011
DOI: 10.1371/journal.pone.0016898
|View full text |Cite|
|
Sign up to set email alerts
|

Male-Specific Transfer and Fine Scale Spatial Differences of Newly Identified Cuticular Hydrocarbons and Triacylglycerides in a Drosophila Species Pair

Abstract: We analyzed epicuticular hydrocarbon variation in geographically isolated populations of D. mojavensis cultured on different rearing substrates and a sibling species, D. arizonae, with ultraviolet laser desorption/ionization mass spectrometry (UV-LDI MS). Different body parts, i.e. legs, proboscis, and abdomens, of both species showed qualitatively similar hydrocarbon profiles consisting mainly of long-chain monoenes, dienes, trienes, and tetraenes. However, D. arizonae had higher amounts of most hydrocarbons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…LDI-MS more efficiently detects polar CHC (e.g. oxygen-containing compounds), many of which are not detected by GC/MS (supplementary material Fig.S2) (Yew et al, 2009), as well as particular long-chained hydrocarbons (Yew et al, 2011a), but it does not detect alkanes. Because only intact molecular ions are detected and thus no structural information is obtained, the stereochemistry of a compound cannot be elucidated.…”
Section: Results and Discussion Aging Robustly Alters Chc Profiles Inmentioning
confidence: 99%
See 1 more Smart Citation
“…LDI-MS more efficiently detects polar CHC (e.g. oxygen-containing compounds), many of which are not detected by GC/MS (supplementary material Fig.S2) (Yew et al, 2009), as well as particular long-chained hydrocarbons (Yew et al, 2011a), but it does not detect alkanes. Because only intact molecular ions are detected and thus no structural information is obtained, the stereochemistry of a compound cannot be elucidated.…”
Section: Results and Discussion Aging Robustly Alters Chc Profiles Inmentioning
confidence: 99%
“…We closely followed the method outlined by Yew and colleagues (Yew et al, 2009;Yew et al, 2011b) for detecting CHC by LDI-MS. To account for biological variability, quantitative data were derived by averaging the signal intensities obtained from 3-5 individual flies for each age and genotype. Flies were anesthetized and mounted with fine forceps onto adhesive tape (G304, Plano GmbH, Wetzlar, Germany), which was attached to a glass coverslip.…”
Section: Ldi-ms Analysismentioning
confidence: 99%
“…However, it has been unclear whether they are actually present on the epicuticle or merely co-extracted from the fat body or other internal tissues (Buckner, 1993). Recent studies using ultraviolet laser desorption/ionization mass spectrometry demonstrated the presence of TAGs on the cuticle of Drosophila flies (Yew et al, 2011), but a communicative function has never been shown so far.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pheromones have been manipulated in order to control the population growth of agricultural pests and disease-bearing insects [2]. Recently, we showed that ultraviolet laser desorption ionization orthogonal time-of-flight mass spectrometry (UV-LDI o-TOF MS) allows analysis of cuticular hydrocarbons and triglycerides directly from the external cuticle of individual fruit flies [3][4][5]. Direct UV-LDI MS provides spatially-resolved analysis of HCs without chemical extraction or the addition of a matrix to the cuticle.…”
Section: Introductionmentioning
confidence: 99%